2019
DOI: 10.1515/cclm-2019-0428
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsy of cerebrospinal fluid identifies neuronal pentraxin receptor (NPTXR) as a biomarker of progression of Alzheimer’s disease

Abstract: Background Alzheimer’s disease (AD) is the most prevalent form of dementia. Currently, the most studied biomarkers of AD are cerebrospinal fluid (CSF) amyloid β 1-42, total tau and phosphorylated tau. However, misdiagnosis can exceed 20%. Recently, we found that CSF amyloid β precursor-like protein-1 (APLP1) and neuronal pentraxin receptor (NPTXR) are promising biomarkers of AD. The aim of the present study is to validate CSF APLP1 and NPTXR as biomarkers of AD severity. Methods APLP1 and NPTXR concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…NPTXR is a transmembrane synaptic protein belonging to the neuronal pentraxin family. NPTXR plays a role in organisation of excitatory and inhibitory synapses by interaction with neuronal pentraxin 1 and 236 and lower CSF levels were also reported for Alzheimer’s disease and multiple sclerosis 37 38. Interestingly, NPTXR levels were not significantly altered in sFTD cases compared with non-neurodegenerative controls in our study, although we observed a trend to lower CSF levels.…”
Section: Discussionsupporting
confidence: 63%
“…NPTXR is a transmembrane synaptic protein belonging to the neuronal pentraxin family. NPTXR plays a role in organisation of excitatory and inhibitory synapses by interaction with neuronal pentraxin 1 and 236 and lower CSF levels were also reported for Alzheimer’s disease and multiple sclerosis 37 38. Interestingly, NPTXR levels were not significantly altered in sFTD cases compared with non-neurodegenerative controls in our study, although we observed a trend to lower CSF levels.…”
Section: Discussionsupporting
confidence: 63%
“…233,234 All 3 neuronal pentraxins have lately received much attention and have been shown in several studies to have decreased CSF levels in AD and MCI groups compared with controls. 231,[235][236][237][238][239][240][241][242] CSF pentraxin levels also correlate with cognitive performance and hippocampal volume. 150,242,243 Few studies have been performed on other diseases but NPTXR has also been associated with other neurological diseases such as MS 244 and FTD.…”
Section: Emerging Synaptic Biomarkersmentioning
confidence: 99%
“…NPTX1 and NPTX2 are secreted from presynaptic membranes, form oligomeric complexes with NPTXR, and bind extracellular matrix proteins and regulate clustering of neurotransmitter receptors [25]. NPTX1 has been shown to decrease in AD CSF by targeted MS/MS [26] and NPTXR during AD progression [27,28]. NPTX1 and NPTXR have been shown to decrease in CSF from patients with atypical parkinsonian disorders [19].…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%